2021
DOI: 10.3389/fcell.2021.679806
|View full text |Cite
|
Sign up to set email alerts
|

Apatinib Suppresses Gastric Cancer Stem Cells Properties by Inhibiting the Sonic Hedgehog Pathway

Abstract: The presence of gastric cancer stem cells (GCSCs) marks the onset of gastric carcinoma. The sonic hedgehog (SHH) pathway plays a vital role in the maintenance of GCSC characteristics. Apatinib has been approved in China for advanced gastric cancer (GC) treatment. However, whether apatinib can target GCSCs and affect the SHH pathway remains unclear. The present study aimed to investigate the underlying mechanism of apatinib’s antitumor effects on GC. The expression levels of GCSC markers and number of CD133+ ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“… Ge et al (2019) found that sulforaphane suppresses the stemness of GC stem cells by inhibiting the Hedgehog pathway. It is reported that Apatinib suppresses GC stem cells properties via inhibiting the Hedgehog pathway ( Cao et al, 2021 ). Low levels of DIM promoted GC progression by activating the Wnt4 pathway to enhance GC cell stemness ( Zhu et al, 2016 ).…”
Section: Effects Of Phytochemicals On the Occurrence And Development ...mentioning
confidence: 99%
“… Ge et al (2019) found that sulforaphane suppresses the stemness of GC stem cells by inhibiting the Hedgehog pathway. It is reported that Apatinib suppresses GC stem cells properties via inhibiting the Hedgehog pathway ( Cao et al, 2021 ). Low levels of DIM promoted GC progression by activating the Wnt4 pathway to enhance GC cell stemness ( Zhu et al, 2016 ).…”
Section: Effects Of Phytochemicals On the Occurrence And Development ...mentioning
confidence: 99%
“…[17][18][19][20] Preclinical studies have shown that apatinib exerts antitumor effects in gastric cancer through a variety of mechanisms. [21][22][23] A previous study that enrolled 273 patients with gastric cancer who progressed after chemotherapy, demonstrated that apatinib treatment significantly improved median PFS and DCR compared with the placebo group. 24 Apatinib has been approved as a third line treatment option for advanced or metastatic gastric cancer or GEJ in China.…”
Section: Discussionmentioning
confidence: 99%
“…Wanshuang Cao et al found that Apatinib can inhibit the stemness of GC cells through the Hedgehog signaling pathway. The specific mechanism is that Apatinib acts by inhibiting the key protein SMO in the Hedgehog signaling pathway [ 147 ]. P H Nguyen et al found that all-trans retinoic acid targets GCSCs and inhibits patient-derived gastric carcinoma tumor growth.…”
Section: Drugs For Gc Treatment By Targeting Its Stemnessmentioning
confidence: 99%